Frequency division multiplexed imaging: A Texas Instruments DMD implementation - Habibkhani, Houman; Güntürk, Bahadır Kürşat; Feldman, Martin; Batur, Aziz Umut (SPIE-Int Soc Optical Engineering SPIE, 2014)
Recently we proposed frequency division multiplexed imaging (FDMI), which allows capturing multiple images in a single shot through spatial modulation and frequency domain filtering. This is achieved by spatially modulating the images so that different images or sub-exposures are placed at different locations in the Fourier domain. As long as there is no overlap of the individual bands, we can recover different components by band-pass filtering the multiplexed image. In this paper, we present a Texas Instruments DMD based implementation of FDMI. An image is formed on the DMD chip; pixels are modulated by the micro-mirrors; and the modulated image is captured by a camera. By applying modulation during a sub-exposure period, the corresponding sub-exposure image is at the end recovered from the full-exposure image. Such a system could be used in a variety of applications, such as motion analysis and image deblurring. We will provide experimental results with the setup, and discuss possible applications as well as limitations.
Conference on Emerging Digital Micromirror Device Based Systems and Applications VI -- FEB 04-05, 2014 -- San Francisco, CA
WOS: 000336032300014
Emerging Digital Micromirror Device Based Systems and Apllications VI
Keywords: Computational Photography; Frequency Division Multiplexing; Digital Micromirror Device